1963
DOI: 10.1152/jappl.1963.18.2.255
|View full text |Cite
|
Sign up to set email alerts
|

Rheology of blood and flow in the microcirculation

Abstract: Rheological properties of normal human blood as a homogeneous substance: its yield stress and the stress-shear rate function under creeping shear rates, were directly measured for the first time in a Couette type viscometer, the cylinders of which were grooved to minimize heterophase effects (defined herein). The experimental data are well fitted by the Casson equation, which implies reversible aggregation of red cells into rouleaux at low shear rates. In particular, the value of yield stress extrapolated from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

1964
1964
2013
2013

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(20 citation statements)
references
References 0 publications
1
19
0
Order By: Relevance
“…Curve A shows a group of canine blood samples with an DISCUSSION As first shown by Brundage (7), the apparent viscosity of blood depends on the shear rate of the flow. This shear rate dependence has lately been confirmed by many authors (5,(8)(9)(10)(11) cause this phenomenon was observed in all blood samples without exception we conclude that red cell aggregation is a normal feature of normal red cells suspended in plasma of normal protein composition. "Aggregation" is seen as a reversible grouping of red cells suspended in plasma, the formation or breakup of the aggregates depending on the flow conditions.…”
Section: Resultssupporting
confidence: 83%
“…Curve A shows a group of canine blood samples with an DISCUSSION As first shown by Brundage (7), the apparent viscosity of blood depends on the shear rate of the flow. This shear rate dependence has lately been confirmed by many authors (5,(8)(9)(10)(11) cause this phenomenon was observed in all blood samples without exception we conclude that red cell aggregation is a normal feature of normal red cells suspended in plasma of normal protein composition. "Aggregation" is seen as a reversible grouping of red cells suspended in plasma, the formation or breakup of the aggregates depending on the flow conditions.…”
Section: Resultssupporting
confidence: 83%
“…Although the cascade of complex interactions from platelet activation, aggregation, and thrombus formation is qualitatively well studied; 35,38,40,41 a systematic screening of the specific interaction of immobilized and circulating VWF and thrombocytes (VWF initiated platelet arrest) and the impact of VWF glycosylation has so far not been provided. This also calls for reducing the system to its main players.…”
Section: Resultsmentioning
confidence: 99%
“…The principle of this viscometer, which consists of coaxial cylinders separated by a small anulus in which the sample is located has been described (26,27). Utilizing a water bath connected to a channel inside the rotor and a thermistor connected to a thermo regulator at the exit from the channel, sample temperature could be maintained at +0.1°0C.…”
Section: Introductionmentioning
confidence: 99%